Possibility of critical practice in computational design: applications on boundaries between public and private space - Laurence Kimmel (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
Computational design technologies enable the shaping of complex transformative surfaces that tend to blur the limits between spaces of different statuses. This article focuses on the possibility of developing artistic and critical practices of computational design: enabling “event” in the evolving architectural system, thus creating “affect”. The possibility to play on boundaries within spaces of different statuses necessitates maintaining the notions of public and private space (as these differences tend to be erased by technologies and their capabilities to connect all space in the same economic network) in order to enable creative intertwining. The possibility of transforming boundaries raises the question of what and who controls them. By keeping a distance between the extremes of total freedom and reaching a so-called “ultimate good” on the one side and of restricted freedom through excessive “law” on the other, the article presents ways for communities to regain control of their environment through new technologies, as long as “common law” of public life is respected. The way parameters and algorithms could be set to function in this model is utopian, although, according to theories of “emergence”, theoretically feasible in the future. Safeguarding the possibility of events and creative singularities in the system upholds a space for critical thinking in architecture that takes into account memory and the will for a better future.